2021
DOI: 10.9734/air/2021/v22i430305
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Why has Africa been “Spared”?

Abstract: After more than one year of the COVID-19 pandemic, the disaster predicted in Africa by experts has not occurred. The present review aimed to discuss factors which may have played an important role in this low incidence. The analysis of data provided by the WHO database and the ECDC (European Center for Disease Prevention and Control) was made. Using explicit reasoning and existing data, the most significant factors were listed and discussed. We found that Africa had the lowest percentage of COVID-19 cases per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Even as the gap between 2019 and 2020 monthly births had been widening throughout 2020, December, which was the earliest it would be reasonable to expect to see an association between COVID-19 and pregnancy intention (9 months following the first widespread outbreaks in the US), stood out, with a 7.7% decrease compared with 2019, 2 percentage points higher than the average decrease across the previous 4 months . Reports from both the Brookings Institution and the Center for American Progress highlight the many ways in which the economic effects resulting from the pandemic have disproportionately affected women, especially working mothers. A survey by The Pew Charitable Trusts found that, between February and August 2020, the time frame of our study, 3 times as many women who were mothers of small children lost their jobs as men who were fathers; in September, the discrepancy increased to 4 times as many .…”
Section: Discussionmentioning
confidence: 99%
“…Even as the gap between 2019 and 2020 monthly births had been widening throughout 2020, December, which was the earliest it would be reasonable to expect to see an association between COVID-19 and pregnancy intention (9 months following the first widespread outbreaks in the US), stood out, with a 7.7% decrease compared with 2019, 2 percentage points higher than the average decrease across the previous 4 months . Reports from both the Brookings Institution and the Center for American Progress highlight the many ways in which the economic effects resulting from the pandemic have disproportionately affected women, especially working mothers. A survey by The Pew Charitable Trusts found that, between February and August 2020, the time frame of our study, 3 times as many women who were mothers of small children lost their jobs as men who were fathers; in September, the discrepancy increased to 4 times as many .…”
Section: Discussionmentioning
confidence: 99%
“…However, currently, women earn low wages and engage in jobs with relatively higher insecurity (Hayghe, 1997). Further, being in vulnerable jobs, they are first to be laid off when there is an economic shock like COVID‐19 (Bateman & Ross, 2020; Grown & Sanchez‐Paramo, 2020). These economic inequalities increase gender differences in political preferences and voting behavior among males and females.…”
Section: Introductionmentioning
confidence: 99%